Interactions of the immunocompetent cells in bronchial asthma - Marsetyawan HNE Soesatyo, Marsetyawan HNE Soesatyo (Universitas Gadjah Mada, 1995)
The presence of immunocompetent cells in the respiratory tract and their cellular interactions are undoubtedly crucial, leading to the development of bronchial asthma in hypersensitive individuals. The cells comprise various populations, such as mast cells, basophils, eosinophils, neutrophils, macrophages, dendritic cells and lymphocytes, in which the T-cells are believed to play a central role. It has been demonstrated that CD4+ T-cells consist of CD45RO reactive population and CD45RA, each secreting different cytokines. In terms of cytokine pattern production, these T-cell subpopulations are similar, to those found in the murine system, i.e. TH1 and TH2 cells. The CD45RO+ IL-4 and IL-2 cells produce directly or indirectly that govern the proliferation and differentiation of B-cells to IgE-secreting plasma cells, by which IgE antibodies are responsible for the development of allergic type I reaction. In addition, the number of T-cells expressing activation markers, like IL-2R, VLA-1 and HLA-DR increases in the serum of asthmatic patients, as well as in their bronchoalveolar lavage and bronchial biopsies. Moreover, the CD4+ T-cells produce IL-3, GM-CSF, IL-4, IL-5, IL-6 and IL-10 that induce mast cell differentiation and activation and recruitment of eosinophils. The function of dendritic cells and macrophages in antigen presentation to either naive or activated T-cells should be noted. Finally, immunologic-based therapy for the airways hyperreactivity may be proposed. This concept includes the regulation of certain cytokine production governing TH1 subpopulations, and by eliciting an optimal mucosal IgA response to down-regulate the production of IgE antibodies.Key Words: bronchial asthma - immunocompetent cell interactions - T-cell subpopulations - T-cell cytokines - mucosal IgA response